On the Formalization Method of Intensional Relations in Konstantinas Raičinskis’ Theory of Concepts - Vaišvila, Alfonsas (Problemos, 1973)
In 1933, Konstantinas Raičinskis, a student of the Theologo-Philosophical Faculty (Department of Philosophy) of Kaunas University, wrote the diploma paper “Mathematical Methods in Logic”, and was conferred the degree of Bachelor of Philosophy. It was the first paper in Lithuania on mathematical logic. It consists of two parts: a general and a special (theory of properties). The paper discussed a number of important questions of mathematical logic. The problem of formalizing intensional relations between concepts is of peculiar interest. Konstantinas Raičinskis suggested a new method which envisaged different symbols for the content and the form of a concept, the concept as a whole being expressed by a combination of the symbols. The aim of the method was to make formalization in logic more complete.